(untitled) (TEL Tempo, Espaço e Linguagem, 2022)
Abstract: Through a brief bibliographic synthesis, it presents, through some intellectuals and their reflections, basic aspects for the historical understanding of post-colonial and decolonial studies, which open possibilities for thinking about multiple perspectives of understanding about history and human sociability, mainly in relation to coloniality and its implications for the colonized.